Health‐related quality of life among migrant workers: The impact of health‐promoting behaviors. (31st October 2019) - Cho, Sunghye; Lee, Hyeonkyeong; Oh, Eui Geum; Kim, Gwang Suk; Kim, Yong‐Chan; Park, Chang‐gi
Abstract: Health‐related quality of life is an important aspect of migrant workers' overall well‐being and adaptation. The aims of this study were to develop a structural model and test the health‐related quality of life among migrant workers. A cross‐sectional study design was used, and data were collected from 228 migrant workers from China who are currently living in Korea and using the services of free clinics for health issues. The structured questionnaire disseminated for the study was designed to measure health‐related quality of life, health‐promotion behaviors, barriers, resources, and perceptual factors. Structural equation modeling was used to test the hypotheses. Health‐promotion behaviors and self‐efficacy have significant positive direct effects on health‐related quality of life, and acculturative stress has a significant negative direct effect on health‐related quality of life. These findings suggest that certain strategies are needed for developing health‐promotion programs aimed at the betterment of migrant workers' health‐related quality of life. Specifically, health‐promotion behaviors and self‐efficacy among migrant workers should be encouraged, and strategies for decreasing their acculturative stress should be formulated.